Analysis of provisions and contingent liabilities in companies listed on B3 - Espindula, Gabriella Janete; Souza, Maíra Melo de (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Purpose: Analyze the level of mandatory and voluntary disclosure of provisions and contingent liabilities in Brazilian publicly traded companies. Methodology: A sample of 406 companies listed on B3 was observed. To analyze the level of mandatory and voluntary disclosure, two checklists were created based on the determinations of accounting pronouncement CPC 25. Results: The most recurrent types of provisions and possible and remote contingent liabilities existing in the companies in the sample were, respectively: labor, civil and tax. The sectors with the highest levels of provision disclosure were: Public Utilities, Health and Information Technology. In relation to Possible Contingent Liabilities, the highest levels of disclosure of companies that made a profit were observed in the Health, Public Utilities and Non-Cyclical Consumption sectors. Regarding voluntary disclosure, the Public Utility and Cyclical Consumption sectors presented a higher average of disclosure and a higher average of expressiveness, which may represent possible tendencies of these sectors to disclose their remote contingencies. Contributions of the Study: The research contributes to the literature by demonstrating how Brazilian public companies are dealing with the disclosure of their provisions and contingent liabilities, addressing mandatory and voluntary disclosure in these situations, which are relevant because they have a high potential impact on the results of the year, if they are not disclosed, it is expected to pose risks to investors and other external users of the company.